Investigating The Language Learning Strategy Used By English Department Students At Madako University - Hasia Marto; Marzuki; Diyenti Rusdin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2021)
This research aims at Investigating the Language Learning Strategy Used by English Department Students at Madako University. The type of this research is qualitative research. The samples were 15 students at B class which were selected purposively. Its data were collected through questionnaire. The result showed that students used all the strategies including memory, cognitive, compensation, metacognitive, affective and social strategy. The most strategy used by the students were metacognitive strategy. And it showed, students used metacognitive strategy (20%), followed by the social strategy (18%), compensation strategy (16%), affective strategy (16%), cognitive strategy (15%), and memory strategy (15%). The result also showed the students were categorized as high language learning strategy users.